X-ray Spectroscopic Verification of the Active Species in Iron-Catalyzed Cross-Coupling Reactions - Schoch, Roland; Desens, Willi; Werner, Thomas; Bauer, Matthias (Chemistry : a European journal, 2013)
X‐ray absorption: The activation of the pre‐catalyst as well as the catalytically active species and reaction mechanism of Fe‐catalyzed cross‐couplings were investigated by X‐ray absorption spectroscopy. The active catalytic components are small iron clusters with three to four FeI centers. The reaction seems to proceed by an FeI/FeIII mechanism (see figure).